Protecting Personal Data: Access Control for Privacy Preserving Perimeter Protection System - Rath, Annanda Thavymony; Colin, Jean-Noël (Data and Applications Security and Privacy XXIX, 2015)
In this paper, we address the issues of personal data protection for privacy preserving perimeter protection system, particularly, the access control for real-time data streamed from surveillance tools and also for data stored in facility’s storage. Furthermore, we also provide an access control model proposed specifically for such system and access control system implemented in Java.